REVOLUTIONIZE THE POTENTIAL OF CHATGPT AS TEACHING MATERIAL TO ENGAGE STUDENTS IN LEARNING - A. Ramli Rasyid; Ahmad Al Yakin; Muthmainnah Muthmainnah; Saidna Zulfiqar Bin Tahir; Ahmed J. Obaid (Lentera Pendidikan: Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Since ChatGPT was released to the public, several students have used it for academic purposes. This study aimed to investigate the feasibility of implementing ChatGPT as teaching material to motivate students to learn. This study used a survey method through a questionnaire to obtain data. The respondents of this research were the students of the Engineering faculty at Makassar State University, consisting of 77 students. The instrument used was a questionnaire using the Likert scale. Data were analyzed using SPSS version 26. The findings of this study highlighted that most respondents believed that ChatGPT as teaching material impacted students’ motivation to learn Pancasila and citizenship education courses. The implications of this research are to motivate students to learn, and the lecturers should prepare their materials with the appropriate technology, design effective teaching models, and develop curricula and learning activities that can improve comprehensive understanding of the material being taught, the right learning resources, the right technology, and the right teaching instructions.